Canada's First Nations And Cultural Genocide - Robert Z. Cohen
For more than 100 years, Canada$1 (Bs First Nations, Inuits, and Metis people endured an educational system designed to essentially remove all evidence of their native identities. Children were mistreated and stripped of their identities as they were (3z(Beducated(3y (Bin the ways of a nation that wanted no trace of the (3z(BIndian.(3y (BThis insightful resource provides a history of Canada and outlines the development of attitudes that resulted in the residential education system, as well as a glimpse into the experiences of children who made it through. Readers will also learn about efforts to help a nation continue to heal.s